2007
DOI: 10.1017/s1751731107000407
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high and low dietary crude protein and inulin supplementation on nutrient digestibility, nitrogen excretion, intestinal microflora and manure ammonia emissions from finisher pigs

Abstract: A 2 3 2 factorial experiment was performed to investigate the interaction between a high-and low-crude-protein (CP) diet (200 v. 140 g/kg) and inulin supplementation (0 v. 12.5 g/kg) on nutrient digestibility, nitrogen (N) excretion, intestinal microflora, volatile fatty acid (VFA) concentration and manure ammonia emissions from 24 boars (n 5 6, 74.0 kg live weight). The diets were formulated to contain similar concentrations of digestible energy and lysine. Pigs offered the high-CP diets had a higher excreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 46 publications
5
25
1
Order By: Relevance
“…There was a significantly lower CTTAD of CP in rabbits fed the chicory diets, a finding that is consistent with similar findings in rats (Levrat et al, 1993;Vanhoof and De Schrijver, 1996) and pigs (Lynch et al, 2007;Hedemann and Knudsen, 2010) when inulin-rich diets were fed. Additionally, the CTTADs of EE and starch were significantly lower in rabbits fed the chicory diets, probably because of the higher ADF/starch ratio of these diets (Gidenne et al, 2000).…”
Section: Discussionsupporting
confidence: 89%
“…There was a significantly lower CTTAD of CP in rabbits fed the chicory diets, a finding that is consistent with similar findings in rats (Levrat et al, 1993;Vanhoof and De Schrijver, 1996) and pigs (Lynch et al, 2007;Hedemann and Knudsen, 2010) when inulin-rich diets were fed. Additionally, the CTTADs of EE and starch were significantly lower in rabbits fed the chicory diets, probably because of the higher ADF/starch ratio of these diets (Gidenne et al, 2000).…”
Section: Discussionsupporting
confidence: 89%
“…This equals a 5% reduction in ammonia emission per day per 10 g/kg reduction in CP. Lynch et al (2007) reported a 6.6% reduction in ammonia emissions per 10 g/kg reduction in dietary CP in vitro while Hayes et al (2004) achieved an 8.1% reduction per 10 g/kg CP in vivo. The 42% reduction in N excretion as dietary CP was reduced to 150 g/kg means that there may be less ammonical N available for volatilisation in the low-CP diet.…”
Section: Discussionmentioning
confidence: 97%
“…The reductions found in the current study in total N excretion may be in agreement with those reported in previous studies (Canh et al, 1998b;Carpenter et al, 2004). Lynch et al (2007) reported a 6% reduction in total daily N excretion for each one-percentage unit reduction in dietary CP to 148 g/kg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been highlighted in many studies which report that the presence of nitrogenous compounds (primarily as urea in urine) along with a high manure pH are the main factors leading to NH 3 emissions from manure (Lynch et al 2007;Feilberg and Sommer 2013). The potential of reduced CP in animal diets to decrease both the amount of N and pH of manure has been demonstrated in various studies (Canh et al 1998;Lynch et al 2007;Le et al 2009). Due to concerns of farmers regarding animal productivity and also due to the safety margins implemented by the feeding industries, dietary CP is usually fed in excess of what is required by the animals.…”
Section: Introductionmentioning
confidence: 98%